Socio-economic wellbeing: lifestyle and ecological impact of the orang asli batek after flood crisis - Abdullah, Sharifah Zahhura Syed (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2017)
Food insecurity occurs whenever people have limited availability of safe and nutritious food or unable to acquire them in socially acceptable ways. This cross-sectional study assessed food insecurity and nutrttional status among 38 Batek women (15-55 years old) after recent massive 'Bah Kuning' in Pos Lebir, Kuala Krai, Kelantan. Respondents were interviewed for socioeconomic and demographic data, as well as information on household food security and dietary intake. They were examined for weight, height and waist and hip circumferences. For analysis of data, descriptive statistics was used. All of the respondents experienced household food insecurtty as assessed using the Radimer/Cornell Hunger and Food Insecurity instrument. In general, all of the food insecure households were living below the poverty line; with most of them had no education; and mothers as housewives. Approximately 36.8% of the respondents were underweight while 10.5% and 5.3% were overweight and obese respectively. Waist hip ratio for majority of the respondents showed that they were less likely to suffer from heart disease and cardiovascular problems. The present study also indicated that among this sample of indigenous women, the relationship between food insecurity and obestty is a complex one, which involves the interaction with other factors. Nevertheless, given that obesity and food insecurity are public health concerns in the developing nations, the association between these two aspects should be further investigated.